Amaranthus tamariscinus Nutt. (Amaranthaceae): taxonomical notes on the species and its presence in Italy - Duilio Iamonico (Natura Sloveniae)
Based on a historical-nomenclatural study and examination of type material and Italian specimens, Amaranthus tamariscinus Nutt. is to be considered a casual alien species for Friuli-Venezia Giulia and Italy. The identity of the species is also discussed.